Altered hippocampal volume and functional connectivity in patients with Cushing's disease. Issue 6 (4th May 2022) - Li, Chuqi; Zhang, Yanyang; Wang, Wenxin; Zhou, Tao; Yu, Xinguang; Tao, Hong
Abstract: Introduction: Stress‐related brain disorders can be associated with glucocorticoid disturbance and hippocampal alteration. However, it remains largely unknown how cortisol affects the structure and function of hippocampus. Cushing's disease (CD) provides a unique "hyperexpression model" to explore the effects of excessive cortisol on hippocampus as well as the relation between these effects and neuropsychological deficits. Methods: We acquired high‐resolution T1‐weighted and resting‐state functional magnetic resonance imaging in 47 CD patients and 53 healthy controls. We obtained the volume and functional connectivity of the hippocampal rostral and caudal subregions in both groups. Relationships between hippocampal alterations, neuroendocrine, and neuropsychological assessments were identified. Results: Relative to control subjects, the CD patients had smaller volumes of all four hippocampal subregions. Furthermore, whole brain resting‐state functional connectivity analyses with these four different hippocampal regions as seeds revealed altered hippocampal functional connectivity with high‐order networks, involving the DMN, frontoparietal, and limbic networks in CD patients. The intrinsic hippocampal functional connectivity was associated with the quality of life of the CD patients. Conclusions: Our findings elucidate the cumulative effect of excess cortisol on the morphology and function of hippocampus and reinforce the need for effective interventions in stress‐related brain disease to halt potential hippocampal damage. Abstract : 1. CD patients had significant atrophy of all four hippocampal subregions. 2. Altered hippocampal functional connectivity with high‐order networks was found in CD patients. 3. Effective interventions are needed to halt potential hippocampal damage in stress‐related brain disease.